The Power Of Ideas - DIRECHS, Claudia (Nias Press, 2006)
This book brings a new approach to the study of political change in East and Southeast Asia and demonstrates the importance of political odeas behind policies and politics. The traditional approach to studying the politics of a region is to focus on event, personalities, issues - the mechanics of the political process.